Bcl-2-mediated control of TRAIL-induced apoptotic response in the non-small lung cancer cell line NCI-H460 is effective at late caspase processing steps. - Lubna Danish; Dirke Imig; Frank Allgöwer; Peter Scheurich; Nadine Pollak (PLoS ONE, 2018)
Dysregulation of the mitochondrial signaling pathway of apoptosis induction represents a major hurdle in tumor therapy. The objective of the presented work was to investigate the role of the intrinsic (mitochondrial) apoptotic pathway in the non-small lung cancer cell line NCI-H460 upon induction of apoptosis using the highly bioactive TRAIL derivative Db-scTRAIL. NCI-H460 cells were TRAIL sensitive but an only about 3 fold overexpression of Bcl-2 was sufficient to induce a highly TRAIL resistant phenotype, confirming that the mitochondrial pathway is crucial for TRAIL-induced apoptosis induction. TRAIL resistance was paralleled by a strong inhibition of caspase-8, -9 and -3 activities and blocked their full processing. Notably, especially the final cleavage steps of the initiator caspase-8 and the executioner caspase-3 were effectively blocked by Bcl-2 overexpression. Caspase-9 knockdown failed to protect NCI-H460 cells from TRAIL-induced cell death, suggesting a minor role of this initiator caspase in this apoptotic pathway. Rather, knockdown of the XIAP antagonist Smac resulted in enhanced caspase-3 degradation after stimulation of cells with TRAIL. Of note, downregulation of XIAP had only limited effects on TRAIL sensitivity of wild-type NCI-H460 cells, but resensitized Bcl-2 overexpressing cells for TRAIL-induced apoptosis. In particular, XIAP knockdown in combination with TRAIL allowed the final cleavage step of caspase-3 to generate the catalytically active p17 fragment, whose production was otherwise blocked in Bcl-2 overexpressing cells. Together, our data strongly suggest that XIAP-mediated inhibition of final caspase-3 processing is the last and major hurdle in TRAIL-induced apoptosis in NCI-H460 cells, which can be overcome by Smac in a Bcl-2 level dependent manner. Quantitative investigation of the XIAP/Smac interplay using a mathematical model approach corroborates our experimental data strengthening the suggested roles of XIAP and Smac as critical determinants for TRAIL sensitivity.